Creating good conditions for innovation-driven productivity gains in Australia - Hemmings, Philip (OECD Publishing, 2017)
Innovation is key to boosting Australia's productivity and inclusiveness. This paper examines the policies that create good conditions for innovation, not only in science and technology but also wider forms, such as business-model innovation. Competition and flexible markets are particularly important in the Australian context. Also there is room to improve the environment for firm entry and exit, and intellectual property arrangements. However, the returns to public spending on Australia's numerous innovation-related SME support schemes are uncertain. Federal and state governments are taking a positive approach to the new wave of "disruptive" service-sector innovations, such as those underway in personal transport, accommodation, legal and financial services. Harnessing the full benefits of today's innovation requires household and business have access to high-speed ICT; and there is room for improvement on this front in Australia. In education, Australia's STEM-oriented strategy could be strengthened. Innovation in public-services should receive considerable attention as this can raise aggregate productivity and improve living standards
Keywords: Economics; Australia